Study of african swine fevervirus reproduction in porcine primary bone marrow cell culture before and after cryopreservation - I. Yu. Zhukov; I. V. Shevchenko; N. N. Vlasova; A. A. Varentsova; B. L. Manin; O. S. Puzankova; V. L. Gavrilova; A. S. Igolkin (Ветеринария сегодня)
This paper presents data on the preparation of cells from porcine bone marrow, spleen, lymph nodes, kidneys and testicles used for African swine fever virus reproduction. Viability of cells after cryopreservation was studied only in porcine bone marrow cell culture. The cell culture was frozen and stored at -70, -150 and -196°C. 10% dimethyl sulfide supplemented with 10% of fetal bovine serum was used as a cryoprotectant. When the cells were thawed and the cryoprotectant was removed 10 lU/ml of heparin sodium was added to prevent cell aggregation. ASFV culturing in porcine bone marrow cell culture stored at -150 and -196°C during 5-6 months demonstrated the highest haemadsorption titers: 5,76±0,25 Ig HAdU50/0,15 cm3 and (4,66-4,87)±0,25 Ig HAdU50/0,15 cm3, respectively. Porcine bone marrow cells remained viable only for four months of storage at -70°C and were able to maintain the virus reproduction at the level of (3,2-3,86)±0,25 Ig HAdU50/0,15 cm3 when thawed.